2020
DOI: 10.1186/s12917-020-02475-4
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of labetalol as antihypertensive agent in dogs

Abstract: Background To evaluate the effect on arterial blood pressure (ABP) of labetalol infusion as treatment for perioperative non nociceptive acute hypertension in dogs. The clinical records of dogs receiving intra or postoperative labetalol infusion were retrospectively reviewed. Invasive systolic (SAP), mean (MAP) and diastolic (DAP) arterial pressure and heart rate (HR) before labetalol infusion (T0) and 15, 30, 45 and 60 min (T1, T2, T3 and T4 respectively) after infusion were retrieved. The dose ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Labetalol performed favourably in a recent cohort of dogs undergoing surgery with intra‐ and postoperative non‐nociceptive hypertension (Zublena et al . 2020). Fenoldopam has been recommended for use in veterinary patients with hypertensive emergency based on its safety profile in patients with AKI (Nielsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Labetalol performed favourably in a recent cohort of dogs undergoing surgery with intra‐ and postoperative non‐nociceptive hypertension (Zublena et al . 2020). Fenoldopam has been recommended for use in veterinary patients with hypertensive emergency based on its safety profile in patients with AKI (Nielsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…A randomized control trial revealed that labetalol control BP (mean systolic and diastolic BP) in pregnant women with chronic hypertension 47 . According to a recent study, labetalol reduced arterial blood pressure in dogs with a non-significant increase in heart rate as a therapy for perioperative non-nociceptive acute hypertension 48 .…”
Section: Practololmentioning
confidence: 99%
“…Herrera et al reported that dogs pretreated with phenoxybenzamine undergoing adrenalectomy for pheochromocytoma had a mortality rate of 13% compared to 48% of dogs that were not pretreated 10 . Labetalol has also been investigated as a medication to treat acute hypertension peri‐operatively for dogs undergoing adrenalectomy 11 . More recently, the use of pre‐operative alpha‐blocker therapy has been brought into question with pretreatment not associated with increased survival 5 .…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Several studies have investigated the role of medical pretreatment to decrease complications and perioperative mortality, specifically with pheochromocytomas. 5,7,10,11 Despite a growing a body of literature relating to adrenalectomies in dogs, however, a consensus on peri-operative management has not been obtained to reduce surgical risk. Herrera et al reported that dogs pretreated with phenoxybenzamine undergoing adrenalectomy for pheochromocytoma had a mortality rate of 13% compared to 48% of dogs that were not pretreated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation